Komunitas Makrozoobenthos, Bahan Organik dan Fraksi Sedimen di Perairan Sungai Siak Kota Pekanbaru - Teda Sanodri; Eni Sumiarsih; Nur El Fajri El Fajri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Community structure of benthic organisms can be used as indicator to understand the quality of aquatic ecosystem in general. Siak River received many types of pollutants that mainly produced by anthropgenic activities conducted along the river bank and it may negatively affects the benthic organisms living in the river. To understand the macrozoobenthos community structure, organic matter and sediment fractions of the Siak River. There were 4 stations (St1 was in the area with no anthropogenic activity; St 2 was around the rubber factory; St 3 was around the oil processing factory and St 4 was around palm oil plantation). Samplings were conducted 2 times, April and June 2016. Samples were then identified and analyzed. Results shown that there were eight types of macrozoobenthos captured, Acuticosta sp. Tubifex sp., Bittium sp., Oncomelania sp., Tricula sp., Pila sp., Chironomus sp. and Limnodrilus sp. There was dominant species, namely Tricula sp. In all research sites, the organic matter content was ranged from 2.78 to 13.23%. In the St 1, 2 and 3 the sediment was sandy mud, while that of the St 4 was muddy sand. Based on data obtained, it can be concluded that the Siak River is heavily polluted.Keywords: Siak River, Macrozoobenthos, Organic Materials, Sediment Fraction